METODE CERDAS BERBAHASA INDONESIA FONIK DALAM PELAKSANAAN PEMBELAJARAN PENGEMBANGAN BAHASA - Winda Dwi Putri; M Nasirun; Anni Suprapti (Jurnal Ilmiah POTENSIA, 2017)
The purpose of this research was to describe the implementation of language learning development by using Cerdas Berbahasa Indonesia (CBI) phonic method at Islamic Kindergarten Auladuna in Bengkulu city. This research used descriptive quantitative method and the subject of the research was 14 teachers in class A and B. The data of the research were gathered by using observation and interviews and analyzed by using percentage and average formula. The result of the research showed that the teachers have implemented language learning development by using Cerdas Berbahasa Indonesia (CBI) phonic method on excellent category, the implementation of language learning development by using Cerdas Berbahasa Indonesia (CBI) phonic method at Islamic Kindergarten Auladuna in Bengkulu city has led to the provision and guidance of the implementation of language learning development by using Cerdas Berbahasa Indonesia (CBI) phonic method, the teachers who carry out the most activities were the teachers of NM, and teachers who carry out the least avtivities were SZ teachers. For suggestion, in implementing language learning development by using Cerdas Berbahasa Indonesia (CBI) phonic method, the researcher should make a schedule and regular timing for each group of children in order to create an effective learning and the activities can be done equally.